EDUKASI MENGENAI MANFAAT KONSUMSI IKAN SEBAGAI ASUPAN GIZI DALAM MENJAGA KESEHATAN TUBUH SISWA SMA N 11 KOTA PADANG - Primadella Della Fegita; Muhammad Rizki Saputra (Stikes Syedza Saintika Padang, 2022)
Background: Nutrients are components in foodstuffs that break down during the digestive process in the body, including water, carbohydrates, proteins, fats, vitamins, and minerals. Fish is a second-class source of animal protein after meat, milk and eggs. Fish is a marine product that contains long-chain fatty acids: omega‐3 (DHA) that is less owned is not even possessed by land products (animal and vegetable) and omega‐6.Method: In this service activity are presentations and lectures on fish as the best and safest source of food for the health of the human body, discussions and questions and answers. Before this service activity was carried out, several stages of activity were first carried out, including preliminary observations made to find out the condition of the school and the existing problems. Furthermore, collaborating with the school is carried out to support the success of the program.Result: At the time of this socialization, the antosiasm of the students and students was very visible, this was evidenced by the number of questions that arose regarding the material being mapped. So far, they have never received fish socialization material as the best and safest food source for health clearly and completely.Keywords: Nutrition,fish,students